Sex disparities in completeness of revascularisation and outcomes in patients with ST-elevation myocardial infarction and multivessel coronary artery disease. (25th November 2020) - Mahdi, N; Har, B; Graham, M.M; Basha, A; Bizios, A
Abstract: Background: In patients with ST-elevation myocardial infarction (STEMI) and multivessel coronary artery disease (CAD), complete revascularisation is associated with reduced mortality compared to culprit only revascularisation. However, there are limited data regarding the relationship between sex and revascularisation strategy in STEMI with multivessel CAD and outcomes. Purpose: Our aim is to evaluate sex related differences in treatment strategies and outcomes in patients with STEMI and multi-vessel CAD. Methods: We included all consecutive patients from a provincial registry presenting with STEMI and multivessel CAD treated with percutaneous coronary intervention (PCI) from 2008–2015. The study population consisted of 856 females and 3152 males who were treated with culprit vessel only PCI or complete revascularisation using staged-PCI. The outcomes were death, admission for acute coronary syndrome (ACS), and admission for heart failure (HF). Multivariate Cox proportional hazard models were used to examine the association between treatment strategy and outcomes. Backward stepwise logistic regression was used to identify predictors of patients undergoing staged-PCI versus culprit vessel only PCI. Results: At 3 years, the incidence of death was higher in females than males (15.9% vs. 8.2%, p<0.001), as were HF admissions (10.3% vs. 5.0%, p<0.001). Females underwent less staged-PCI than males (10.4% vs. 14.8%; adjusted odds ratio 0.75; 95% CI 0.57–0.97). Younger age and increasing Duke jeopardy score were also associated with performing staged-PCI. After adjusting for baseline characteristics, females had a higher risk of death (HR 1.35; 95% CI 1.07–1.71), ACS admission (HR 1.27; 95% CI 1.00–1.60), and HF admission (HR 1.38; 95% CI 1.03–1.85). Following additional adjustment for revascularisation strategy, only death and HF admission remained significant. Females undergoing staged-PCI had similar survival to males (figure), with no significant interaction between revascularisation strategy and sex (p for interaction = 0.19) Conclusion: Females with STEMI and multivessel CAD were less likely to be treated with complete revascularisation by staged-PCI and had worse outcomes when compared to males. Survival in both males and females treated with staged-PCI was similar. Our study suggests that addressing the lack of complete revascularisation in females presenting with STEMI may improve outcomes. Funding Acknowledgement: Type of funding source: None